Genotypic Diversity of Streptococcus mutans in Caries-Free and Caries-Active Preschool Children - F. J. S. Pieralisi; M. R. Rodrigues; V. G. Segura; S. M. Maciel; F. B. A. Ferreira; J. E. Garcia; R. C. Poli-Frederico (International Journal of Dentistry)
Aim. The aim of the present paper was to evaluate the genotypic diversity of S. mutans in caries-free and caries-active preschool children in Brazil. Design. Twenty-eight preschool children were examined regarding caries experience by the dmft index. DNA from 280 isolates of S. mutans was extracted. S. mutans evaluated using to the PCR method, with primers for the glucosyltransferase gene. The genetic diversity of S. mutans isolates was analyzed by arbitrary primed-PCR (AP-PCR) reactions. The differences between the diversity genotypic and dmft/caries experience were evaluated by 𝜒2 test and Spearman's correlation. Results. The Spearman correlation test showed a strong association between genotypic diversity and caries experience (𝑟=0.72; 𝑃<.001). There were more S. mutans genotypes in the group of preschool children with dental caries, compared with the caries-free group. Among the children with more than 1 genotype, 13 had dental caries (2 to 5 genotypes) and 4 were caries-free (only 2 genotypes). Conclusion. Our results support the previous findings of genetic diversity of S. mutans in preschool children being associated with dental caries. The investigation of such populations may be important for directing the development of programs for caries prevention worldwide.